Mortality, Causes of Death and Risk Factors for Death Among Primary Amphetamine Users in the Swedish Criminal Justice System. (1st February 2014) - Ericsson, Emmy; Bradvik, Louise; Hakansson, Anders
<x xml:space="preserve">Abstract</x> This study examined mortality and predictors of death in 1, 396 primary amphetamine users (85% males) who were interviewed with the Addiction Severity Index in the Swedish criminal justice system during 2000–2006 and followed through 2008. Forty-nine clients deceased (standardized mortality ratio 4.1 [3.0–5.4]), at least 84% of deaths were violent or drug-related (12% suicides), and Cox regression analysis indicated that death was associated with frequent use of sedatives and less frequent use of amphetamine. No female deaths were observed; death and male gender were associated in binary analysis. Implications for diagnostics and treatment are discussed.